León Anguiano, B. (2024). Grandes comunicadores de la Ciencia. De Galileo a Rodríguez de la Fuente. Comares editorial. - Teso Alonso, Maria Gemma (Estudios sobre el Mensaje Periodístico, 2024)
The book Grandes comunicadores de la Ciencia. De Galileo a Rodríguez de la Fuente is the result of a project by the professor and researcher at the University of Navarra Bienvenido León, published by Editorial Comares in 2024.This is a book that breaks down the keys and strategies of science communication in a different format than usual, as it does so through ten stories dedicated to ten men and women of science who lived in different places and historical periods, but who knew how to adapt to the conditions of the century in which they lived in order to bring knowledge to wider audiences. Each chapter is dedicated to a renowned scientific figure and constitutes an independent story, built around the life of a character chosen for their contributions to science and for their ability and commitment to communicating knowledge.